THE JURISDICTION OF INTELLECTUAL PROPRIETARY RIGHTS OF NAMBO WEAVING AFFAIRS OF BANGGAI REGENCY - Rahmat Setiawan; Firmansyah Fality (JCH (Jurnal Cendekia Hukum), 2021)
Nambo weaving is a local wisdom as the pride of the people in Banggai Regency. As the heritage of the artistic art of local weaving affais which has the artistic value deserves to be excelled by acclamated the Nambo Weaving as the land mark for tourism sectors in Banggai District of Central Sulawesi. The practical purpose of this article is to observe the jurisdiction of Intellectual Proprietary Rights and the efforts to provide legal protection for the existence of Nambo Weaving. Empirical legal research is as method of the research; specifically is based on the sociological juridical type. Sociological juridical research is research based on normative legal science and its implementation. The results showed that legal protection of Intellectual property rights for Nambo Weaving can be done by protecting the Geographical Indication. The safeguard that has been done is registration of Geographical Indications of Nambo Weaving. However, the registration process is still pending at the substantive examination stage. As for the efforts made to support legal protection of Intellectual property rights for Nambo Weaving are by optimizing the registration process for the Geographical Indication for Nambo Weaving, registering the copyright for Nambo Weaving motifs and providing guidance to craftsmen.